Imports and the structure of retail markets - Horst Raff; Nicolas Schmitt (Kiel University, Department of Economics, 2011)
We construct a model of trade with heterogeneous retailers to examine the effects of trade liberalization on retail market structure, imports and social welfare. We are especially interested in investigating the transmission of lower import prices into consumer prices and the effects of retail market regulation. The paper shows that changes in import prices may have large effects on consumer prices and import volumes when changes in retail market structure are taken into account, and that restrictions on retailing, as they occur in several countries, may significantly alter this transmission mechanism by reducing imports and raising consumer prices.
Keywords: F12; L11; 330; International trade; retailing; firm heterogeneity; Außenhandelsliberalisierung; Außenhandelspreis; Einzelhandel; Marktstruktur; Einzelhandelspreispolitik; Einzelhandelspolitik; Theorie